Dietary fiber in plant cell walls—the healthy carbohydrates. (13th January 2022) - An, Yi; Lu, Weitai; Li, Wenze; Pan, Langlang; Lu, Mengzhu; Cesarino, Igor; Li, Zheng; Zeng, Wei
Abstract: Dietary fiber (DF) is one of the major classes of nutrients for humans. It is widely distributed in the edible parts of natural plants, with the cell wall being the main DF-containing structure. DF content varies significantly in different plant species and organs, and the processing procedure can have a dramatic effect on the DF composition of plant-based foods. Given the considerable nutritional value of DF, a deeper understanding of DF in food plants, including its composition and biosynthesis, is fundamental to the establishment of a daily intake reference of DF and is also critical to molecular breeding programs for modifying DF content. In the past decades, plant cell wall biology has seen dramatic progress, and such knowledge is of great potential to be translated into DF-related food science research and may provide future research directions for improving the health benefits of food crops. In this review, to spark interdisciplinary discussions between food science researchers and plant cell wall biologists, we focus on a specific category of DF—cell wall carbohydrates. We first summarize the content and composition of carbohydrate DF in various plant-based foods, and then discuss the structure and biosynthesis mechanism of each carbohydrate DF category, in particular the respective biosynthetic enzymes. Health impacts of DF are highlighted, and finally, future directions of DF research are also briefly outlined.